Design of the Variable Inclination Continuous Transverse Stub Antenna Based on Rectangular Grating Slow-Wave Structure - Jun Gao; Xue Lei; Guo-Hu Chen; Yi Zhang; Jun-Mo Wu (International Journal of Antennas and Propagation)
In order to solve difficulty in designing nonlinear slow-wave structure (SWS) of the variable inclination continuous transverse stub (VICTS) antenna, we combine the study of the semiopen rectangular grating SWS in the PPW with equivalent circuit theory of leaky-wave antenna to propose a theoretical model for SWS of VICTS element. The computations that the propagation characteristics of VICTS element are calculated by the theoretical model. The results are consistent with the full-wave simulation, which prove the validity and accuracy of the theoretical model. Lastly, by using the theoretical model, an approach for nonlinearly designing SWS is introduced and carried out. The approach improves the gain of the VICTS antenna 0.4 dB.